PENGEMBANGAN INSTRUMEN PENILAIAN PEMBELAJARAN DI SMA IBRAHIMY WONGSRSEREJO BANYUWANGI - Junaidi Junaidi; Taufiqurrahman Taufiqurrahman (LP2M Universitas Ibrahimy, 2020)
Assessment is a critical factor for successful learning. Assessment is part of instructional design system. Assessment and learning are related as cycles that occur before, during and after learning; diagnostic, formative and summative. Effective learning embodies a variety of appropriate and consistent assessments. This outreach involved all teachers at SMA Ibrahimy Wongsorejo, Banyuwangi as part of the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo. This ability is the most important ability in learning evaluation. From that assessment a teacher can know the abilities that have been mastered by the students. Teachers must know basic competencies (KD) that have been mastered by the students. The teacher makes a self-reflection from the activities that have been done. To get the expected target, it is necessary to instill four awareness for the teachers. They are sense of goal (goal), sense of regulation (regularity), sense of achievement (achievement), and Sense of harmony (harmony). The process of mentoring at SMA Ibrahimy Wongsorejo was conducted in several stages: initial mapping, building relationships with school members, participatory mapping, agenda setting, implementation, and reflection. This outreach process can transform knowledge and practice